Efficiency factors in 110-metre hurdle clearance techniques: kinematics among specialist hurdlers and decathletes - Hamda Mansour; Mounira Ben Chaifa; Ibrahim I. Atta; Majed M. Alhumaid; Mohamed Ahmed Said (Termedia Publishing House, 2024)
Purpose Technical differences may explain why elite hurdles specialists (EHS) and elite decathletes (ED) perform differently in the 110-metre hurdles. This study aims to compare the hurdle-unit kinematic parameters in EHS and ED. Methods A total of 20 male athletes were recruited, including 10 EHS (age: 20.9 ± 2.2 years, body mass: 76.9 ± 7.0 kg, height: 1.85 ± 0.05 m) and 10 ED (age: 20.8 ± 2.27 years, body mass: 87.7 ± 6.9 kg, height: 1.91 ± 0.03 m). Their three-dimensional movement was analysed for hurdling sequences over the whole hurdle-crossing phase and the entire cycle of the first stride after the hurdle, with spatial, temporal, and angular characteristics compared between groups. Results EHS were characterised by faster hurdle crossing (p = 0.002), shorter stride length over the hurdle (p = 0.002), and a shorter support phase in the first stride post-hurdle (p = 0.005). The centre of mass (CM) path of ED was higher than that of EHS (p = 0.003). EHS attack the hurdle with the lead leg's knee significantly more flexed (p = 0.001) and after crossing the hurdle, regain contact with the ground with the lead leg more flexed at the hip level (p = 0.004), the trunk more inclined forward (p = 0.01), and a relatively smaller positioning angle of the supporting leg (p = 0.021). Conclusions EHS can be identified by their reduced impulse time, abbreviated take-off phase over the hurdle, and accelerated landing. Furthermore, EHS achieved optimum speed between obstacles faster, resulting in less speed loss and enhanced performance.